MIXED LIGAND COMPLEXES BASED ON 2, 2, 2 - TRICHLORO - N - ( DIPIPERIDIN - 1 - YL - PHOSPHORYL) ACETAMIDE: UDC 543.42+546.182+546.6 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
On the base of 2,2,2-trichloro-N-(dipiperidin-1-yl-phosphoryl)acetamide (HL) two rows of the coordination compounds LnL3·α,α'-Dipy and LnL3·Phen (Ln = La, Ce-Nd, Sm-Lu, Y) have been synthesized and characterized by means of IR, UV-VIS, 1Н, 31Р NMR spectroscopy.  The ligand HL and the compound TbL3Phen were investigated by X-Ray analyses. It was determined, that deprotonated ligand is coordinated in a bidentate-cyclic manner via the oxygen atoms of the carbonyl and phosphoryl groups.
Keywords: -